Prevalence of risk factors and severity level of diabetic retinopathy in UiTM Medical Specialist Centre: an ordinal analysis - Che Jani, Aniza Ayuna; Khairudin, Zuraida; Mohd Razali, Nornadiah; Abd Aziz, Nor Azimah; Abd Rahman, Hezlin Aryani; Abu Bakar, Nur Syamimi (Universiti Teknologi MARA, 2025)
Diabetic Retinopathy (DR) has become a major concern as the number of diabetic patients who are diagnosed with DR has been on the rise each year. Hence, the adoption of a strategic approach is needed to determine the factors that contribute to the level of severity in DR patients. This research aims to determine the significant risk factors influencing the severity level of DR as well as to evaluate the classification rate between the severity level of 157 patients at UiTM Private Specialist Centre by employing the Ordinal Logistic Regression (OLR) analysis. The study revealed that there were 60 (38%) patients with Mild NonProliferative Diabetic Retinopathy (NPDR), 61 (39%) patients with moderate NPDR, 9 (6%) patients with severe NPDR and 27 (17%) patients with Proliferative Diabetic Retinopathy (PDR). On top of that, the severity level of DR was found to be influenced by the duration of diabetes melitus (DM) (p=0.005), nephropathy (p=0.011) and dyslipidemia (p=0.035). Patients who did not have nephropathy were 0.6 times less likely and patients who did not have the dyslipidemia were 0.7 times more likely to have the highest severity level of DR compared to lower severity levels. For the duration of DM, an increase in the duration was associated with an increase in the odds of having the highest severity level. Finally, the results showed that severity level 2 (Mild NPDR), severity level 3 (Moderate NPDR) and severity level 4 (Severe NPDR) were the most accurate categories predicted by the model. This study can contribute to the improvement of health among DR patients and provides alternatives to the hospital in giving treatments to the patients.